Endocrine side effects of immune checkpoint inhibitors - Zulma Cardona; Jeffrey A. Sosman; Sunandana Chandra; Wenyu Huang (Frontiers in Endocrinology, 2023)
Immune checkpoint inhibitors (ICIs) have increasingly been the mainstay of treatment for numerous malignancies. However, due to their association with autoimmunity, ICIs have resulted in a variety of side effects that involve multiple organs including the endocrine system. In this review article, we describe our current understanding of the autoimmune endocrinopathies as a result of the use of ICIs. We will review the epidemiology, pathophysiology, clinical presentation, diagnosis, and management of the most commonly encountered endocrinopathies, including thyroiditis, hypophysitis, Type 1 diabetes, adrenalitis, and central diabetes insipidus.